Poetics of black bodies, from Brazil to Madrid: reverberations: réverbérations (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This essay proposes to discuss the possibilities of meeting for four shows that were conceived in different contexts, Brazil and Spain, by black artists, based on a creative proposition based on black theaters. For this writing, I sought to relate my theoretical propositions about black theaters with the epistemological contributions proposed by Conceição Evaristo, Leda Martins, Onisajé and Soraya Martins Patrocínio, as I believe that such propositions, in some way, are present in the plays Macacos, by Clayton Nascimento; Undercover in Vox, by Moha Gerehou; Black Man Solo, by Malcolm McCarthy; and El vuelo del Hipotálamo, by José Ramón Hernández.
Keywords: Black Man Solo; Infiltrados en Vox; El vuelo del Hipotálamo; Macacos; poetics of bodies